China Satellite Navigation Conference (CSNC) 2015 proceedings - Sun, Jiadong; Liu, Jingnan; Fan, Shiwei; Lu, Xiaochun (Springer Berlin Heidelberg, 2015)
China Satellite Navigation Conference (CSNC) 2015 Proceedings presents selected research papers from CSNC2015, held during 13th-15th May in Xian, China. The theme of CSNC2015 is Opening-up, Connectivity and Win-win. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 10 topics to match the corresponding sessions in CSNC2015, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications. SUN Jiadong is the Chief Designer of the Compass/ BDS, and the academician of Chinese Academy of Sciences (CAS); LIU Jingnan is a professor at Wuhan University. FAN Shiwei is a researcher at China Satellite Navigation Office; LU Xiaochun is an academician of Chinese Academy of Sciences (CAS).